A Survey on web services in telecommunications. - Griffin, Donna; Pesch, Dirk.
This article presents a survey of service-oriented architecture and Web services within telecommunications. Telecommunications over the past few years has been in a state of constant flux, with shifts in regulations, increased competition, and technological progress. The article describes these forces in detail and shows that the need for successful adoption of SOA within telecommunication has become a major agenda item for the majority of telecommunication network operators. The article then proceeds to describe SOA and its key enablers in telecommunications - Web services, event-driven architectures, Parlay X/ECMA specifications, and the enterprise service bus.
Keywords: Parlay X/ECMA specifications; Web services; Enterprise service bus; Event driven architecture; Service oriented architecture; Telecommunications